Community, culture, and economic development : continuity and change in two small southern towns - Ramsay, Meredith, 1937- (State University of New York Press, 2013)
"Newly updated comparative study of economic development policy, and its relationship with local power structures and cultural and social relations, in two Maryland towns"--Provided by publisher.